Peran Media Sosial sebagai Alat Public Relations Mengatasi Stereotip Negatif PT Victory International Futures : Penelitian - Rewanda Mutiara Az-Zahra Rahmadina; Siti Aminah (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Public Relations plays a crucial role in shaping a company’s image, especially for brokerage firms that often face negative stereotypes from the public. This study aims to analyze the role of social media as a Public Relations tool in overcoming negative perceptions toward brokerage companies, with a case study at PT Victory International Futures, Ciputra World Branch. The research uses a descriptive qualitative approach, focusing on the company’s social media communication strategies. Data were collected through observation, interviews with the Public Relations division, and documentation of social media content. The results show that social media platforms such as Instagram and TikTok are effectively used to deliver educational messages, promote transparency, and build trust among audiences. Through consistent content and interactive engagement, the company successfully improves its public image and reduces negative stereotypes. This study concludes that social media serves as a strategic and impactful medium for modern Public Relations activities, particularly in industries facing public skepticism such as brokerage firms, in a sustainable and audience-oriented manner.